Impact of COVID-19 on Nepali Migrant Workers and Social Safety Schemes at Destination - Khatiwada, Padma Prasad (Journal of Social Protection, 2020)
The Coronavirus disease (COVID-19) has had an enormous impact on Nepali migrant workers. By 15 September 2020, altogether 63,347 people returned home via rescue flights coordinated by the Government of Nepal. It is estimated that about 200,000 Nepalese are waiting to be repatriated. This article first examines the status of, and challenges and vulnerabilities faced by, Nepali migrant workers in the context of COVID-19. It then highlights the social security schemes offered by different countries of destination for the migrant workers. Key finding suggests that most of the migrant workers had low educational backgrounds. They had experienced changes in working hours after COVID-19. Although different safety measures were adopted at the workplace, they were largely insufficient, while on the other hand, the local residents in the destination countries treated the migrants negatively. Moreover, the destination countries were found to be giving less attention towards the social security schemes for the migrant workers.